Human biomarkers: can they help us to develop a new tuberculosis vaccine?. (June 2016) - Fletcher, Helen A; Dockrell, Hazel M
The most effective intervention for the control of infectious disease is vaccination. The BCG vaccine, the only licensed vaccine for the prevention of tuberculosis (TB) disease, is only partially effective and a new vaccine is urgently needed. Biomarkers can aid the development of new TB vaccines through discovery of immune mechanisms, early assessment of vaccine immunogenicity or vaccine take and identification of those at greatest risk of disease progression for recruitment into smaller, targeted efficacy trials. The ultimate goal, however, remains a biomarker of TB vaccine efficacy that can be used as a surrogate for a TB disease end point and there remains an urgent need for further research in this area.